Osteopontin attenuates aging‐associated phenotypes of hematopoietic stem cells. (15th May 2017) - Guidi, Novella; Sacma, Mehmet; Ständker, Ludger; Soller, Karin; Marka, Gina; Eiwen, Karina; Weiss, Johannes M; Kirchhoff, Frank; Weil, Tanja; Cancelas, Jose A; Florian, Maria Carolina; Geiger, Hartmut
Abstract :